2018
DOI: 10.1371/journal.pone.0200276
|View full text |Cite
|
Sign up to set email alerts
|

Expectations for dog ownership: Perceived physical, mental and psychosocial health consequences among prospective adopters

Abstract: Dog ownership is popular worldwide, with most human-dog dyads forming successful attachment bonds. However, millions of dogs are surrendered to animal shelters annually, possibly due to mismatches between owner expectations and the realities of dog ownership. The aim of the current study was to explore the benefits and challenges people expect from dog ownership and how these expectations vary with previous ownership history. An Australian-wide sample of 3465 prospective adopters completed a self-administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 50 publications
4
51
0
Order By: Relevance
“…Indeed, it may eventually lead to the CA failing to meet the owner's expectations, impaired pet welfare and irresponsible pet ownership, breaking the owner-animal relationship, and at the worst animal relinquishment. Previous studies have pointed to the need for targeted education of the potential pet owners to ensure their expectations be aligned with the reality of pet ownership [39] and to reduce relinquishments [40]. For example, Plitman et al [41] found that owners of brachycephalic cats were less inclined to get due information prior to buying the cat and that, once owning it, they did not consider their cats healthy (in particular due to their skin and eye condition), as compared with the owners of other pedigree cats.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it may eventually lead to the CA failing to meet the owner's expectations, impaired pet welfare and irresponsible pet ownership, breaking the owner-animal relationship, and at the worst animal relinquishment. Previous studies have pointed to the need for targeted education of the potential pet owners to ensure their expectations be aligned with the reality of pet ownership [39] and to reduce relinquishments [40]. For example, Plitman et al [41] found that owners of brachycephalic cats were less inclined to get due information prior to buying the cat and that, once owning it, they did not consider their cats healthy (in particular due to their skin and eye condition), as compared with the owners of other pedigree cats.…”
Section: Discussionmentioning
confidence: 99%
“…Companion animal guardianship has been linked with improved physical and psychological outcomes, including lower blood pressure [1,2], reduced risk of cardiovascular disease and lower rates of mortality [3,4], reduced loneliness [5], and increased emotional support during mental health crisis [6]. In fact, research has indicated that many people choose to keep companion animals for reasons associated with well-being, such as companionship, emotional support, and improved physical health [7,8]. Similarly, animal-assisted interventions (AAI) are initiated with the specific purpose of improving one or more aspects of human well-being; they include goal-oriented animal-assisted therapies delivered by healthcare professionals, and animal-assisted activities which are often volunteer-led and may lack specific treatment goals [9].…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing awareness of the roles that dogs play in the lives of their owners. Dog owners may list many reasons for acquiring a dog and there is increasing research that explores why owners acquire dogs and the associated benefits and challenges of dog ownership [12]. Benefits that dogs may provide include providing support, companionship, social engagement [13], and increased physical activity [14].…”
Section: Introductionmentioning
confidence: 99%